Effect of progesterone on Candida albicans biofilm formation under acidic conditions: A transcriptomic analysis - Bruna Gonçalves; Ruben Bernardo; Can Wang; Markus S. Schröder; Nuno A. Pedro; Geraldine Butler; Joana Azeredo; Mariana Henriques; Nuno Pereira Mira; Sónia Silva (Elsevier, 2020)
Vulvovaginal candidiasis (VVC) caused by Candida albicans is a common disease worldwide. A very important C. albicans virulence factor is its ability to form biofilms on epithelium and/or on intrauterine devices promoting VVC. It has been shown that VVC has a hormonal dependency and that progesterone affects virulence traits of C. albicans cells. To understand how the acidic environment (pH 4) and progesterone (either alone and in combination) modulate C. albicans response during formation of biofilm, a transcriptomic analysis was performed together with characterization of the biofilm properties. Compared to planktonic cells, acidic biofilm-cells exhibited major changes in their transcriptome, including modifications in the expression of 286 genes that were not previously associated with biofilm formation in C. albicans. The vast majority of the genes up-regulated in the acidic biofilm cells (including those uniquely identified in our study) are known targets of Sfl1, and consistently, Sfl1 deletion is herein shown to impair the formation of acidic biofilms (pH 4). Under the acidic conditions used, the presence of progesterone reduced C. albicans biofilm biomass and structural cohesion. Transcriptomic analysis of biofilms developed in the presence of progesterone led to the identification of 65 down-regulated genes including, among others, the regulator Tec1 and several of its target genes, suggesting that the function of this transcription factor is inhibited by the presence of the hormone. Additionally, progesterone reduced the susceptibility of biofilm cells to fluconazole, consistent with an up-regulation of efflux pumps. Overall, the results of this study show that progesterone modulates C. albicans biofilm formation and genomic expression under acidic conditions, which may have implications for C. albicans pathogenicity in the vaginal environment.